Lithium manganese iron phosphate positive electrode material with carbon coating layer and preparation method of lithium manganese iron phosphate positive electrode material

By using a composite carbon source to form a carbon cladding layer in the preparation of lithium manganese iron phosphate positive electrode material, the problems of high specific surface area and high powder resistivity are solved, and processing performance and production efficiency are improved.

CN119890242APending Publication Date: 2025-04-25NANTONG RESHINE NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311375541.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The specific surface area of ​​lithium manganese iron phosphate positive electrode material is relatively high, the powder resistivity is relatively high, and the solid content needs to be improved during pulping, resulting in poor processing performance during battery preparation and production efficiency needs to be improved.

Method used

Using the preparation method of lithium manganese iron phosphate positive electrode material with carbon cladding, by adding a composite carbon source during the secondary sintering process, the carbon in the composite carbon source is distributed on the surface of the particles, forming a carbon cladding layer, reducing the powder resistivity and significantly reducing the specific surface area.

Benefits of technology

The specific surface area and powder resistivity of the positive electrode material are reduced, the solid content is improved, thereby improving the processing performance during battery preparation, reducing battery manufacturing costs, and improving the production efficiency of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890242A_ABST
    Figure CN119890242A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium manganese iron phosphate positive electrode material with a carbon coating layer and a preparation method of the lithium manganese iron phosphate positive electrode material, and relates to the technical field of lithium ion batteries. The preparation method comprises the steps that raw materials and a solvent are evenly mixed, a primary mixture is obtained, and the raw materials comprise a phosphorus-containing compound, a manganese-containing compound, an iron-containing compound, a lithium-containing compound and an additive; performing primary pretreatment and primary sintering on the primary mixture to obtain a primary sintered material; uniformly mixing the primary sintered material, a composite carbon source and a solvent to obtain a secondary mixture, the composite carbon source comprising at least two different carbon-containing compounds; the secondary mixed material is subjected to secondary pretreatment and secondary sintering, and a secondary sintered material is obtained; secondary sintering is carried out, so that carbon in the composite carbon source is distributed on the particle surface of the secondary sintered material, and a carbon coating layer is formed; and carrying out post-treatment on the secondary sintered material to obtain the lithium manganese iron phosphate positive electrode material. The processing performance of the lithium iron manganese phosphate positive electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium manganese iron phosphate positive electrode material with a carbon coating layer and a preparation method thereof. Background Art

[0002] Currently, commercial lithium-ion battery cathode materials primarily include ternary (nickel-cobalt-manganese oxide), lithium manganese oxide, and lithium iron phosphate. Ternary materials offer the highest energy density, but the inclusion of rare metals nickel and cobalt makes them expensive and their safety is relatively poor. Commercial applications require system-level components to prevent thermal runaway, further increasing their cost. Compared to ternary materials, lithium manganese oxide is less expensive, but due to manganese leaching during use, the Jahn-Teller effect leads to poor cycle life, and lithium manganese oxide also has poor safety. Lithium iron phosphate offers significant safety and cost advantages over the other three materials. After years of development in the lithium iron phosphate industry, material design and manufacturing technologies have matured, and its actual performance capacity is approaching its theoretical capacity. Its powder compaction density reaches as high as 2.6g / cc, and its performance potential has been largely fully realized.

[0003] With the continuous development of the new energy industry and the continuous advancement of material technology, the industry's innovation and progress are still continuing in an environment where the above three material systems have become increasingly mature. Among them, a variety of new positive electrode materials have been proposed, developed and applied, including high-voltage spinel nickel-manganese binary materials, lithium-rich manganese-based materials, and lithium iron manganese phosphate materials. Among them, lithium iron manganese phosphate materials have similar safety and capacity to lithium iron phosphate, and their voltage platform is about 0.6V higher than that of lithium iron phosphate. The mass energy density is 10~20% higher than that of lithium iron phosphate materials, and it has a significant energy density advantage. Therefore, lithium iron manganese phosphate materials are regarded as an upgraded version of lithium iron phosphate materials, with significant cost advantages per watt-hour.

[0004] However, there are still many problems in the performance of lithium manganese iron phosphate materials. For example, the specific surface area of ​​the material is relatively high, the powder resistivity is relatively high, and the solid content during slurry preparation needs to be improved, resulting in poor processing performance during battery preparation and the need to improve production efficiency. Summary of the Invention

[0005] The object of the present invention is to provide a lithium manganese iron phosphate positive electrode material with a carbon coating layer and a preparation method thereof, which can improve the processing performance of the positive electrode material during battery preparation.

[0006] To achieve the above object, a technical solution adopted by the present invention is to provide a method for preparing a lithium manganese iron phosphate positive electrode material with a carbon coating layer, comprising: uniformly mixing raw materials with a solvent to obtain a primary mixture, wherein the raw materials include a phosphorus-containing compound, a manganese-containing compound, an iron-containing compound, a lithium-containing compound and an additive; The primary mixed material is subjected to a pre-treatment and a sintering to obtain a primary sintered material; uniformly mixing the primary sintering material, a composite carbon source and a solvent to obtain a secondary mixture, wherein the composite carbon source comprises at least two different carbon-containing compounds; The secondary mixed material is subjected to secondary pretreatment and secondary sintering to obtain a secondary sintered material; the secondary sintering causes the carbon in the composite carbon source to be distributed on the particle surface of the secondary sintered material to form a carbon coating layer; The secondary sintered material is post-processed to obtain the lithium manganese iron phosphate positive electrode material.

[0007] The secondary pretreatment includes coarse grinding, fine grinding and drying; after the coarse grinding, the parameter D50 characterizing the slurry particle size is between 0.5 and 2.0 μm; after the fine grinding, the parameter D50 characterizing the slurry particle size is between 0.2 and 0.5 μm.

[0008] The diameter of the grinding beads used in the coarse grinding is 0.6-1.0 mm, and the diameter of the grinding beads used in the fine grinding is 0.2-0.35 mm.

[0009] The secondary sintering is specifically as follows: heating to a sintering temperature at a rate of 2-5°C / min and sintering for 3-15 hours, wherein the sintering temperature is between 500-850°C.

[0010] Wherein, the sintering temperature is between 600 and 700°C.

[0011] The composite carbon source includes a first carbon source and a second carbon source, the amount of the first carbon source accounts for 2-9% of the total mass of the secondary sintered material, and the amount of the second carbon source accounts for 2-9% of the total mass of the secondary sintered material.

[0012] Wherein, the first carbon source is polyethylene glycol, and the second carbon source is at least one of glucose, sucrose, and starch.

[0013] The first carbon source is polyethylene glycol with a molecular weight between 2000 and 4000, and the second carbon source is glucose.

[0014] The additive is used to dope the lithium manganese iron phosphate positive electrode material with metal elements, and the doped metal element is at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni, and Al.

[0015] In order to solve the above technical problems, another technical solution adopted by the present invention is: providing a lithium manganese iron phosphate positive electrode material with a carbon coating layer prepared according to the preparation method described in the above technical solution.

[0016] The beneficial effects of the present invention are as follows: relative to the prior art, in the preparation method of the lithium iron manganese phosphate positive electrode material provided by the present invention, a composite carbon source is added during the secondary sintering process, so that after the secondary sintering, the carbon in the composite carbon source is distributed on the particle surface of the secondary sintered material to form a carbon coating layer, thereby reducing the powder resistivity of the positive electrode material. Moreover, the application of the composite carbon source can significantly reduce the specific surface area of ​​the positive electrode material, and can increase the solid content of the lithium iron manganese phosphate positive electrode material during slurrying from 50% to 60%, thereby improving the processing performance of the lithium iron manganese phosphate positive electrode material during the battery preparation process, reducing the battery manufacturing cost, and improving the production efficiency of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without inventive efforts. Among them: Figure 1 Schematic diagram of a process for preparing a lithium manganese iron phosphate cathode material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0019] See also Figure 1 , Figure 1 The figure is a flow chart of an embodiment of a method for preparing a lithium manganese iron phosphate positive electrode material according to the present invention. The method comprises the following steps: Step S11 , mixing raw materials and solvent uniformly to obtain a primary mixture, wherein the raw materials include a phosphorus-containing compound, a manganese-containing compound, an iron-containing compound, a lithium-containing compound and additives.

[0020] The raw materials for preparing lithium manganese iron phosphate are the raw materials commonly used in the prior art, the phosphorus-containing compounds are, for example, one or more of phosphoric acid, lithium dihydrogen phosphate, and ammonium dihydrogen phosphate, the manganese-containing compounds are, for example, one or more of manganese dioxide, manganese tetraoxide, and manganese carbonate, the iron-containing compounds are, for example, one or more of ferrous oxalate, ferric phosphate, and ferric oxide, and the lithium-containing compounds are, for example, one or more of lithium dihydrogen phosphate, lithium carbonate, and lithium phosphate.

[0021] Additives include doping compounds. To improve the performance of cathode materials, metal oxides, carbonates, phosphates, and metal organics are often added to the raw materials. These additives are used to achieve metal doping and maintain the material structure. Examples include Mg, Ti, V, Nb, W, Mo, Er, Co, Ni, and Al. Additives also include reducing agents, which are used to reduce iron ions in iron-containing compounds to produce lithium manganese iron phosphate.

[0022] The ratio of the various raw materials is also the ratio commonly used in the prior art, satisfying the element ratio of lithium manganese iron phosphate. Among them, water can be used as the solvent, and stirring or other methods can be used to promote the mixing of the raw materials and the solvent to obtain a uniform primary mixture.

[0023] Step S12: performing a pre-treatment and a sintering on the primary mixed material to obtain a primary sintered material.

[0024] After the raw materials and the solvent are evenly mixed to obtain a primary mixture, it is first subjected to a pretreatment, specifically coarse grinding, fine grinding and drying in sequence. The coarse grinding and fine grinding can be carried out by sand grinding or the like. After grinding to a suitable particle size, it is spray dried to remove the solvent, and then subjected to a sintering treatment to obtain a primary sintered material.

[0025] Step S13: uniformly mix the primary sintering material, the composite carbon source and the solvent to obtain a secondary mixed material, wherein the composite carbon source includes at least two different carbon-containing compounds.

[0026] After obtaining the primary sintered material, it is evenly mixed with a composite carbon source and a solvent. The solvent can be water or other solvents that can dissolve and disperse the primary sintered material and the composite carbon source, wherein the composite carbon source includes at least two different carbon-containing compounds, to obtain a secondary mixture.

[0027] Step S14 , performing secondary pretreatment and secondary sintering on the secondary mixed material to obtain a secondary sintered material; the secondary sintering causes the carbon in the composite carbon source to be distributed on the particle surface of the secondary sintered material to form a carbon coating layer.

[0028] After obtaining the secondary mixture, it undergoes secondary pretreatment, specifically coarse grinding, fine grinding, and drying. The requirements for coarse and fine grinding are that after coarse grinding, the parameter D50, which characterizes the slurry particle size, is between 0.5 and 2.0 μm, and after fine grinding, the parameter D50, which characterizes the slurry particle size, is between 0.2 and 0.5 μm. To achieve this, the diameter of the grinding beads used for coarse grinding is preferably 0.6 to 1.0 mm, and the diameter of the grinding beads used for fine grinding is preferably 0.2 to 0.35 mm.

[0029] The material is then subjected to a secondary sintering, specifically, the temperature is first raised to the sintering temperature at a rate of 2-5°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., and the sintering temperature is maintained at the sintering temperature for 3-15 hours. The sintering temperature is between 500-850°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, etc., preferably between 600-700°C.

[0030] The composite carbon source comprises a first carbon source and a second carbon source, wherein the amount of the first carbon source accounts for 2-9% of the total mass of the secondary sintering material, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc., and the amount of the second carbon source accounts for 2-9% of the total mass of the secondary sintering material, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc. The first carbon source is polyethylene glycol, and the second carbon source is at least one of glucose, sucrose, and starch. Preferably, the first carbon source is polyethylene glycol with a molecular weight between 2000 and 6000, and the second carbon source is glucose.

[0031] During the secondary sintering process, the carbon element in the composite carbon source is enriched on the surface of the material particles, forming a carbon coating layer with excellent conductive properties, which has the effect of reducing the resistivity of the positive electrode material powder.

[0032] Step S15: post-processing the secondary sintered material to obtain lithium manganese iron phosphate positive electrode material.

[0033] After obtaining the secondary sintered material, conventional post-processing operations such as air flow crushing and screening to remove iron are performed on it to obtain a lithium manganese iron phosphate positive electrode material with a carbon coating layer.

[0034] Using the preparation method of the lithium iron manganese phosphate positive electrode material provided in this embodiment, the surface of the obtained positive electrode material particles has a carbon coating layer, which can improve the powder resistivity of the positive electrode material, and the application of the composite carbon source can significantly reduce the specific surface area of ​​the positive electrode material. The solid content of the lithium iron manganese phosphate positive electrode material during slurrying can be increased from 50% to 60%, thereby improving the processing performance of the lithium iron manganese phosphate positive electrode material during the battery preparation process, reducing the battery manufacturing cost, and improving the production efficiency of the battery cell.

[0035] Based on the same inventive concept, the present invention also provides a lithium manganese iron phosphate positive electrode material with a carbon coating layer. The positive electrode material is prepared by the preparation method in the above embodiment. This embodiment has the same beneficial effects as the above embodiment and will not be repeated here.

[0036] Based on the same inventive concept, the present invention also provides a lithium-ion battery, which includes the lithium iron manganese phosphate positive electrode material in the above-mentioned embodiment, and of course also includes a negative electrode material, a separator, an electrolyte, etc. that can be obtained from the scheme disclosed in the prior art. The lithium-ion battery also has the same beneficial effects as the above-mentioned embodiment, which will not be repeated here.

[0037] The performance improvement brought about by the technical solution provided by the present invention is illustrated below with reference to specific embodiments and comparative examples.

[0038] According to the following steps S101-S105, a lithium manganese iron phosphate positive electrode material with a carbon coating layer was prepared, which is recorded as Example 1: In step S101, 17.9 kg of lithium carbonate, 66.9 kg of ferric phosphate, 8.53 kg of glucose (reducing agent), 52 kg of manganese tetraoxide, 69.9 kg of lithium dihydrogen phosphate, 1.803 kg of magnesium carbonate (dopant compound), 0.144 kg of titanium dioxide (dopant compound), and 0.495 kg of niobium pentoxide (dopant compound) are mixed evenly with 220 kg of water to obtain a primary mixture.

[0039] In step S102, the primary mixed material is introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm), and the primary grinding particle size D50 = 1.3 μm; then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3 mm), and the grinding particle size D50 = 0.35 μm; then spray drying is performed, and the spray drying air inlet temperature is 250°C and the air outlet temperature is 90°C; then sintering is performed under inert atmosphere protection conditions, raising the temperature to 650°C at a rate of 3°C / min, keeping the temperature for 7 hours, and finally cooling to obtain a primary sintered material.

[0040] In step S103 , 100 kg of the primary sintering material, 6.8 kg of glucose, 2.0 kg of polyethylene glycol (molecular weight 6000), and 110 kg of water are mixed and stirred uniformly to obtain a secondary mixture.

[0041] In step S104, the secondary mixed material is introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm) to a grinding particle size D50 = 0.8 μm; then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3 mm) to a particle size D50 = 0.3 μm; then spray dried with an air inlet temperature of 250°C and an air outlet temperature of 90°C; then sintered under inert atmosphere protection conditions, heating the temperature to 700°C at a rate of 3°C / min, keeping the temperature for 7 hours, and finally cooled to obtain a secondary sintered material.

[0042] In step S105 , the secondary sintered material is subjected to air flow pulverization and sieving to remove iron, thereby obtaining the lithium manganese iron phosphate positive electrode material of Example 1.

[0043] Example 2 differs from Example 1 in that, in step S103, the amount of the first carbon source, glucose, is 5.5 kg, and the amount of the second carbon source, polyethylene glycol, is 4.0 kg. The other steps are the same, and the lithium manganese iron phosphate positive electrode material of Example 2 is finally obtained.

[0044] Example 3 differs from Example 1 in that, in step S103, the amount of the first carbon source, glucose, is 4.2 kg, and the amount of the second carbon source, polyethylene glycol, is 6.0 kg. The other steps are the same, and the lithium manganese iron phosphate positive electrode material of Example 3 is finally obtained.

[0045] The comparative example differs from Example 1 in that, in step S103, polyethylene glycol is not added, the amount of glucose used is 7.3 kg, and the other steps are the same, and finally the lithium manganese iron phosphate positive electrode material of the comparative example is obtained.

[0046] Please refer to Table 1, which shows a comparison of performance data of the examples and comparative examples. The specific surface area, carbon content, and powder resistivity of the positive electrode materials of Example 1, Example 2, Example 3, and the comparative example were respectively measured, and button batteries were made in the same manner. Then, the parameter 0.1C gram capacity that characterizes the electrical performance was measured using the method disclosed in the prior art.

[0047] As can be seen from Table 1, with the increase in the amount of polyethylene glycol used in the composite carbon source, the specific surface area and resistivity of the material are significantly reduced, the carbon content remains at a considerable level, and the gram capacity also increases slightly. It is speculated that the optimized ratio of the composite carbon source increases the degree of graphitization of the carbon coating layer, significantly reducing the specific surface area and resistivity of the positive electrode material, thereby improving the processing performance of the lithium manganese iron phosphate positive electrode material in the battery preparation process, reducing the battery manufacturing cost, and improving the production efficiency of the battery cell.

[0048]

[0049] The above description is only an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the description and drawings of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material having a carbon coating layer, characterized in that: include: The raw materials are mixed evenly with a solvent to obtain a primary mixture, wherein the raw materials include a phosphorus-containing compound, a manganese-containing compound, an iron-containing compound, a lithium-containing compound and an additive; The primary mixed material is subjected to a pre-treatment and a sintering to obtain a primary sintered material; The primary sintering material, the composite carbon source and the solvent are uniformly mixed to obtain a secondary mixed material, wherein the composite carbon source includes at least two different carbon-containing compounds; The secondary mixed material is subjected to secondary pretreatment and secondary sintering to obtain a secondary sintered material; the secondary sintering allows the carbon in the composite carbon source to be distributed on the particle surface of the secondary sintered material to form a carbon coating layer; The secondary sintered material is post-processed to obtain the lithium manganese iron phosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: The secondary pretreatment includes coarse grinding, fine grinding and drying; after the coarse grinding, the parameter D50 characterizing the slurry particle size is between 0.5 and 2.0 μm, and after the fine grinding, the parameter D50 characterizing the slurry particle size is between 0.2 and 0.5 μm.

3. The preparation method according to claim 2, characterized in that: The diameter of the grinding beads used in the coarse grinding is 0.6-1.0 mm, and the diameter of the grinding beads used in the fine grinding is 0.2-0.35 mm.

4. The preparation method according to claim 1, characterized in that: The secondary sintering is specifically as follows: The temperature is raised to the sintering temperature at a rate of 2-5°C / min, and sintered for 3-15 hours, wherein the sintering temperature is between 500-850°C.

5. The preparation method according to claim 4, characterized in that: The sintering temperature is between 600 and 700°C.

6. The preparation method according to claim 1, characterized in that: The composite carbon source includes a first carbon source and a second carbon source, wherein the amount of the first carbon source accounts for 2-9% of the total mass of the secondary sintering material, and the amount of the second carbon source accounts for 2-9% of the total mass of the secondary sintering material.

7. The preparation method according to claim 6, characterized in that: The first carbon source is polyethylene glycol, and the second carbon source is at least one of glucose, sucrose and starch.

8. The preparation method according to claim 7, characterized in that: The first carbon source is polyethylene glycol with a molecular weight between 2000 and 6000, and the second carbon source is glucose.

9. The preparation method according to claim 1, characterized in that: The additive includes a doping compound, which is used to dope the lithium manganese iron phosphate positive electrode material with metal elements, and the doped metal element is at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni, and Al.

10. A lithium manganese iron phosphate positive electrode material with a carbon coating layer obtained according to the preparation method according to any one of claims 1 to 9.